Lesson Design Of Geometric Sequences Based On The 6-Question Cognitive Theory - Yujie Lin; Ying Zhou; Simin Wang; Tommy Tanu Wijaya (Departement of Mathematics Education, 2020)
The effective teaching design of mathematics should be designed carefully by teachers according to the situation of students' learning and the analysis of teaching materials. Its teaching design should run through the origin and development of knowledge generation, and reasonably ensure the continuity and integrity of teaching. Based on the theory of